Saccharomyces cerevisiae in directed evolution: An efficient tool to improve enzymes - Gonzalez-Perez, David (Landes Bioscience, 2012)
Over the past 20 years, directed evolution has been seen to be the most reliable approach to protein engineering. Emulating the natural selection algorithm, ad hoc enzymes with novel features can be tailor-made for practical purposes through iterative rounds of random mutagenesis, DNA recombination and screening. Of the heterologous hosts used in laboratory evolution experiments, the budding yeast Saccharomyces cerevisiae has become the best choice to express eukaryotic proteins with improved properties. S. cerevisiae not only allows mutant enzymes to be secreted but also, it permits a wide range of genetic manipulations to be employed, ranging from in vivo cloning to the creation of greater molecular diversity, thanks to its efficient DNA recombination apparatus. Here, we summarize some successful examples of the use of the S. cerevisiae machinery to accelerate artificial evolution, complementing the traditional in vitro methods to generate tailor-made enzymes.